Autism, Metaphor and Relevance Theory - WEARING, CATHERINE (Mind & language, 2010)
The pattern of impairments exhibited by some individuals on the autism spectrum appears to challenge the relevance‐theoretic account of metaphor (Carston, 1996, 2002; Sperber and Wilson, 2002; Sperber and Wilson, 2008). A subset of people on the autism spectrum have near‐normal syntactic, phonological, and semantic abilities while having severe difficulties with the interpretation of metaphor, irony, conversational implicature, and other pragmatic phenomena. However, Relevance Theory treats metaphor as importantly unlike phenomena such as conversational implicature or irony and like instances of ordinary literal speech. In this paper, I show how Relevance Theory can account for the prima facie incongruity between its treatment of metaphor and the case of individuals with autism.